The Future of Social Media and Internet Marketing: Social Media Challenges, Consumer Trends, and Ethical MeMes - Carrington , Yerodin (Recent Trends in Arts and Social Studies Vol. 1, 2023)
The Future of Social Media and Internet Marketing: Social Media Challenges, Consumer Trends, and Ethnical MeMes provides insight on a registered member’s usership of social media. It analyzes one’s social media usage for entertainment and necessities during the Coronavirus (COVID-19) Pandemic in 2020. The social impact theory was applied to perceive one’s social influence to partake in social media challenges, trends, and memes. A content analysis and literature review were conducted to evaluate a member’s social influence online. Registered users initiate dares to challenge another members’ ability online while topics trend due to its current popularity. MeMes furnish social, moral, and ethical expressions to communicate a message with some teasing talent for promotional use. The researcher found a user’s involvement in social media challenges, trends, and memes kept people safe and entertained during the COVID-19 quarantine. It also provides an users’ insight on the purpose and attraction of the blogosphere phenomenon.